Repeated granulation silicon-carbon material with self-assembled conductive structure and preparation method and application of repeated granulation silicon-carbon material
By using multiple granulated silicon carbon materials with self-assembled conductive structures in the negative electrode materials of lithium-ion batteries, the performance attenuation problem caused by volume expansion in the prior art during circulation is solved, efficient and stable battery performance is achieved, and production costs and safety risks are reduced.
Patent Information
- Application Number
- CN202411836210.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The volume expansion/contraction of existing lithium-ion battery negative electrode materials during the charging and discharging cycle leads to rapid performance decay, the first time Coulomb efficiency is low, the long cycle stability is poor, and the mass production process has problems of safety risks and high cost.
Multiple-granulated silicon carbon material with self-assembled conductive structure is used to form submicron-scale silicon carbon precursor microspheres through the mixture of carbon source with a softening point of 150-200°C and nano-silicon powder, primary and secondary sintering, carbon enhancer and conductive agent, and the submicron-scale silicon carbon precursor microspheres are formed, and the conductive structure is formed by secondary sintering by a high-temperature coating machine, and the stability of the material is further improved through surface modification.
It has achieved a lithium-ion battery negative electrode material with high first-time Coulomb efficiency, excellent long cycle stability and good rate performance, reducing production costs and safety risks, and is suitable for new energy vehicles and consumer batteries.
Smart Images

Figure CN119812244A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a multi-granulated silicon-carbon material with a self-assembled conductive structure, a preparation method and an application thereof. Background Art
[0002] Lithium-ion batteries are one of the most well-developed energy storage devices. However, the theoretical capacity of commercial graphite anodes for lithium-ion batteries is only 372 mAh g -1 , can no longer meet the needs of the development of the lithium-ion battery market. Silicon-based negative electrode materials, due to their ultra-high theoretical capacity (4200mAh g -1 ) and is considered an ideal alternative to graphite anodes. However, silicon-based anode materials undergo huge volume expansion / contraction (300%) during the charge and discharge cycle, which leads to rapid degradation of electrode performance.
[0003] Silicon-carbon material is a lithium-ion battery negative electrode material with great potential. The addition of carbon can greatly improve the conductivity of silicon. The tight carbon coating can reduce the adverse effects of silicon expansion causing the material to pulverize and fall off the electrode to a certain extent. The uniformly coated carbon layer can also provide a stable structure for the material, which is conducive to the formation of a stable solid electrolyte interface during the cycle, reducing the adverse effects of silicon expansion causing continuous exposure of new interfaces, resulting in the consumption of lithium and the production of new solid electrolyte interfaces, and can improve the long-cycle stability of the battery.
[0004] The industry has conducted extremely extensive and relatively in-depth research on the application of silicon-carbon negative electrode materials. For example, Chinese invention patent CN113644252B discloses a preparation process for nano-scale silicon powder-coated asphalt-derived carbon materials using asphalt as a carbon source, by adding surfactants and silicon high-energy ball milling, and high-temperature carbonization. Although the final product achieves asphalt carbon coating, which improves the conductivity of the silicon-carbon material, it still has an 85% capacity retention rate after 100 cycles at a current density of 0.5C. However, through the SEM image observation of the invention, it was found that the high-energy ball milling method alone is not enough to nano-size micron silicon, and the effect of alleviating silicon expansion still does not meet industrial requirements. In addition, the first coulomb efficiency of the technology is only 78.5%, which limits the application of the material.
[0005] Chinese invention patent application CN116799148A discloses a flaky three-dimensional silicon-carbon electrode and a preparation method. The electrode is prepared by pre-mixing flaky silicon and graphene and then directly slurrying them with a binder and a solvent. A three-dimensional intercalation structure is constructed in which flaky silicon and graphene layers are interlaced horizontally and vertically, which is beneficial to the contact between the flaky silicon and the graphene. The three-dimensional structure is not easily destroyed during the rolling process of the electrode, thereby improving the interface contact and structural stability between the materials. However, the material has the problem of high interface resistance between the silicon and graphene due to the low intrinsic conductivity of silicon. During the direct slurrying process, it cannot be guaranteed that the flaky silicon is completely covered by the graphene material. Partially exposed silicon will directly contact the electrolyte, expand and break during the charge and discharge process of the battery, continuously exposing new interfaces to form SEI films and consume lithium, resulting in poor cycle stability of the prepared electrode material.
[0006] Chinese invention patent application CN117038984A discloses a method for preparing a graphene-based silicon-carbon negative electrode material, which comprises dispersing nano-silicon powder with a particle size of 100-200 nm in a cationic polyelectrolyte, filtering and vacuum drying, and then blending and compounding it with graphene dispersed in an anionic polyelectrolyte. The nano-silicon-graphene composite is then coated with an organic carbon source, molded under a pressure of 10-14 tons, and then pyrolyzed and granulated to obtain a silicon-carbon composite material. The silicon-carbon composite material is then mixed with graphite and coated with an organic carbon source again, and then pyrolyzed at high temperature to obtain a graphene-based silicon-carbon negative electrode material. The silicon particles of this technology can be evenly embedded in the graphene oxide sheet structure through self-assembly. After carbonization, the mixed material of the two has a rich carbon layer on the surface, which provides a good performance. It provides good lithium ion transmission efficiency, the wrinkled space of graphene buffers the volume expansion of nano-silicon, and the molding process increases the volume energy density of the material and improves the cyclic stability of the material. However, the organic carbon source coating method selected by this process is a liquid phase coating process in which asphalt is dissolved in tetrahydrofuran and then mixed with silicon-graphene material and evaporated to dryness. Tetrahydrofuran is a Class 2B carcinogen and is volatile. This process has certain safety risks in scale-up production, and has requirements for operating equipment and high costs. Nano-silicon powder with a particle size of 100-200nm is relatively expensive, and the silicon oxide layer formed on the surface is thicker than nano-silicon powder with a larger particle size, which ultimately leads to the first coulomb efficiency of the prepared material being far below 90%, which is not conducive to the industrial application of the material. Summary of the Invention
[0007] In order to overcome the performance problems of silicon-carbon materials in the prior art such as low first coulombic efficiency, fast long-cycle attenuation, and low specific capacity, and to solve production problems such as mass production process, expensive cost of existing process, complicated steps, and unstable production quality and output, one of the purposes of the present invention is to develop a process with high production process safety and scalable stable production, a multi-granulated silicon-carbon material with high first coulombic efficiency, good rate performance, slow long-cycle attenuation, and a self-assembled conductive structure and a preparation method thereof.
[0008] A second object of the present invention is to provide a multi-granulated silicon-carbon material with a self-assembled conductive structure for use in preparing negative electrode materials for lithium-ion batteries.
[0009] The object of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure comprises the following steps:
[0011] 1) placing a carbon source with a softening point of 150-200° C. and nano-silicon powder in a mixer to mix the mixture to obtain a uniformly mixed material; placing the mixture in a high-temperature coating machine for primary sintering, and passing through a 200-500 mesh sieve to obtain submicron-sized primary granulated silicon-carbon precursor microspheres;
[0012] 2) The primary granulated silicon-carbon precursor microspheres, recarburizer, graphene oxide, cryptocrystalline graphite, and graphite with D50=9-12 μm are placed in a mixer and mixed evenly, and the materials are added to a high-temperature coating machine for secondary sintering to obtain a secondary granulated silicon-carbon composite material.
[0013] To further achieve the purpose of the present invention, preferably, the multi-granulation silicon-carbon material further includes tertiary granulation of the secondary granulation silicon-carbon composite material or surface modification of the secondary granulation silicon-carbon composite material;
[0014] The three-stage granulation of the secondary granulated silicon-carbon composite material is obtained by mixing the secondary granulated silicon-carbon composite material, water-soluble phenolic resin, distilled water, and anhydrous ethanol, stirring, and evaporating to dryness; a layer of amorphous carbon is added to the secondary granulated silicon-carbon composite material;
[0015] The surface modification of the secondary granulated silicon-carbon composite material is to add the secondary granulated silicon-carbon composite material, distilled water and a high molecular surfactant into a dryer, stir, dry and sieve to obtain a silicon-carbon composite material with a hydrophilic surface.
[0016] Preferably, in the three granulation steps, the mass ratio of the secondary granulation silicon-carbon composite material, water-soluble phenolic resin, distilled water, and anhydrous ethanol is 5: (1-2): (8-12): (0.5-2);
[0017] In the surface modification, the polymer surfactant is one or more of polyethylene glycol, polyvinyl pyrrolidone, polyoxyethylene fatty acid ester, sodium carboxymethyl cellulose, and polyoxyethylene fatty acid ester; the mass ratio of the secondary granulated silicon-carbon composite material, distilled water, and polymer surfactant is (2-3):10:(0.04-0.06).
[0018] Preferably, in step 1), the carbon source having a softening point of 150-200° C. is one or more of asphalt, phenolic resin and glucose; and the mass ratio of the carbon source to the nano-silicon sheet is 1:5-2:5;
[0019] In step 2), the recarburizer is one or more of graphite, glucose, needle coke, and phenolic resin; the mass ratio of the primary granulated silicon-carbon precursor microspheres, the recarburizer, graphene oxide, cryptocrystalline graphite, and graphite with D50 = 9 to 12 μm is 50:(2 to 4):(2 to 4):(10 to 20).
[0020] Preferably, the carbon source needs to be crushed by a crusher before use;
[0021] The cryptocrystalline graphite has a Dv50 of less than 1 μm and is also called earthy graphite, which can be used as a recarburizer and battery material.
[0022] The graphene oxide has a thickness of less than 3 nm, a particle size distribution between 20 and 40 μm, and a specific surface area of 40 to 50 m 2 / g.
[0023] Preferably, in step 1), the heating program of the primary sintering is heating from 0 to 180° C. for 1 to 2 hours, keeping at 180° C. for 1 to 2 hours, heating from 180 to 300° C. for 1 to 2 hours, heating from 300° C. to 500° C. for 1 to 2 hours, and keeping at 500° C. for 2 to 4 hours;
[0024] In step 2), the temperature program of the secondary sintering is: heating from 0 to 180° C. for 1 to 2 hours, keeping at 180° C. for 2 to 4 hours, heating from 180 to 400° C. for 40 to 60 minutes, keeping at this temperature for 1 to 2 hours, heating from 400° C. to 900° C. for 100 to 160 minutes, and keeping at 900° C. for 2 to 4 hours;
[0025] Argon gas is added as a protective atmosphere during the primary and secondary sintering processes, and the oxygen content is controlled at 1-5 ppm throughout the process.
[0026] Preferably, the silicon powder is prepared by wet sand milling; the rotation speed of the wet sand milling is 1000-1500 r / min, the sand milling time is 2-6 hours, the particle size Dv50 of the silicon powder after grinding is controlled to be 400-600 nm, and the silicon powder is stored in vacuum packaging; the solvent for the wet sand milling is selected from one or more of diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether and oleic acid, and the solid content is controlled to be 20-50% during sand milling.
[0027] A multi-granulated silicon-carbon material with a self-assembled conductive structure is prepared by the above-mentioned preparation method.
[0028] The present invention describes the application of multi-granulated silicon-carbon materials with self-assembled conductive structures in the preparation of negative electrode materials for lithium-ion batteries.
[0029] Preferably, the preparation of the negative electrode material for a lithium-ion battery is to mix a multi-granulated silicon-carbon material with a self-assembled conductive structure, conductive carbon black and / or single-walled carbon nanotubes, CMC and PAA, make a slurry, and apply it on a copper foil to obtain a negative electrode sheet for a lithium-ion battery; the mass ratio of the multi-granulated silicon-carbon material with a self-assembled conductive structure, carbon black and / or single-walled carbon nanotubes, CMC and PAA is (5-16): (3-2): (0.5-2): 1.
[0030] Compared with the prior art, this invention has the following advantages and beneficial effects:
[0031] 1) The present invention uses cryptocrystalline graphite and graphene oxide as conductive additives to modify the silicon-carbon material to form a self-assembled structure: the carbon source first melts and decokes, and then cracks into carbon during the high-temperature carbonization process. The viscosity of the carbon source itself in the melting stage is conducive to the cross-linking of flaky graphene, forming a two-dimensional cross-linked graphene network that can alleviate the expansion of the silicon-carbon monomer. The cross-linked network of flaky graphene that wraps the silicon-carbon monomer has good mechanical properties; cryptocrystalline graphite can fill some of the gaps where carbon and silicon are not in contact, which is conducive to the release of silicon capacity; the large graphite particle size can serve as the core of the material to realize the assembly of silicon wafers around the graphite particles and the conductive network to form an overall structure, thereby overcoming the capacity attenuation problem caused by the shedding of small particles during long cycles.
[0032] 2) The cross-linked network of the present invention can also synergize with a binder, conductive carbon black, and single-walled carbon nanotubes to achieve connections between graphene cross-linked networks, construct a conductive carbon black, single-walled carbon nanotube and graphene oxide sheet structure, cryptocrystalline graphite, graphite, and a carbon coating layer of silicon-carbon material blended with cryptocrystalline graphite intercalation and graphene oxide wrapping. It bridges between different submicron silicon-carbon microspheres, provides more contact sites for the negative electrode material, accelerates electron transport during the charge and discharge process of the lithium-ion battery, improves the problem of rapid battery capacity decay during long cycles caused by the silicon-carbon material losing contact with the current collector due to silicon pulverization, solves the problem of excessive capacity decay when the silicon-based material is activated under a relatively large current, and improves the long-cycle stability of the battery prepared by the material.
[0033] 3) Different from the existing process of using only high-energy ball milling to composite carbon and silicon, which takes too long and has an excessively large specific surface area after ball milling, resulting in a low initial coulombic efficiency of the material, the present invention adopts a process of first mixing the materials and then using a coating machine for carbonization. This ensures that during the carbonization process, after the carbon source reaches the softening point, a uniform organic carbon layer can be formed on the surface of the nano-silicon powder through the stirring process of the coating machine. In the subsequent high-temperature carbonization process, it is not easy to agglomerate and has a moderate specific surface area. At the same time, the organic carbon layer forms a bond with the silicon nucleus during the carbonization process, giving the material a stable physical structure.
[0034] 4) The high-speed mixing, ball milling, coating machine carbonization, and drying machine mixing and drying processes adopted in the present invention can all be industrially scaled for production. Using a 500L high-temperature VC coating machine, the single batch output can reach 70kg.
[0035] 5) The metallic silicon powder used in the present invention is low in price. The nano silicon powder prepared through the wet sand grinding process has a significantly high first coulombic efficiency, and the particle size of the silicon powder is stable. The particle size of each batch of nano silicon powder is controllable. The selection of nano-scale silicon powder can ensure that the asphalt can be more uniform during coating.
[0036] 6) The multi-granulated silicon-carbon material with a self-assembled conductive structure of the present invention not only has excellent long-cycle performance, but also has extremely good rate performance, and at the same time has a high initial efficiency, which can meet the current market demand for increased specific energy in the field of lithium-ion batteries, and is expected to replace graphite as the next generation of lithium-ion battery negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 These are XRD patterns of the secondary granulated silicon-carbon material with a self-assembled conductive structure prepared in Example 1 and the primary granulated silicon-carbon material prepared in Comparative Example 1.
[0038] Figure 2 This is a TEM image of the secondary granulated silicon-carbon material with a self-assembled conductive structure prepared in Example 1.
[0039] Figure 3 This is an SEM image of the secondary granulated silicon-carbon material with a self-assembled conductive structure prepared in Example 1.
[0040] Figure 4 This is the SEM image of the graphene-based once-sintered granulated silicon-carbon composite material prepared in Comparative Example 2.
[0041] Figure 5 The secondary granulated silicon-carbon material with self-assembled conductive structure prepared in Example 1 was heated to 2Ag. -1 Long cycle performance curve at current density.
[0042] Figure 6 Infrared spectrum of the secondary granulated silicon-carbon material with self-assembled conductive structure prepared in Example 1.
[0043] Figure 7 This is the XPS high-resolution spectrum of Si 2p of the secondary granulated silicon-carbon material with a self-assembled conductive structure prepared in Example 1.
[0044] Figure 8 This is the XPS high-resolution spectrum of C1s of the secondary granulated silicon-carbon material with a self-assembled conductive structure prepared in Example 1.
[0045] Figure 9 The secondary granulated silicon-carbon material with self-assembled conductive structure prepared in Example 1 was heated at 25°C and 0.2Ag -1 The charge and discharge capacity curve of the first three cycles at the current density.
[0046] Figure 10 The secondary granulated silicon-carbon material with self-assembled conductive structure prepared in Example 1 and Example 3 is 0.5-20Ag -1 Rate performance diagram. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with the Examples, Comparative Examples, and accompanying drawings, but the embodiments of the present invention are not limited thereto. It should be noted that any process not specifically described below is readily understood or comprehensible by those skilled in the art with reference to the prior art. Reagents or instruments used without manufacturer indicated are deemed to be commercially available conventional products.
[0048] Cryptocrystalline graphite has a crystal size of less than 1 μm, a carbon content of 60% to 80%, and high mechanical strength. It is one of the conductive agents of the present invention. Unlike large-sized graphene oxide, its smaller particles can be used to build conductive intercalation layers between submicron silicon precursor microspheres. The higher mechanical strength ensures that the conductive structure can still exist stably when silicon expands.
[0049] The present invention uses small-sized cryptocrystalline graphite, graphene oxide, pitch-derived carbon, and large-particle graphite to assemble specific conductive structures. Through sintering processes with stirring functions, ball milling processes, aqueous phase mixing processes, etc., different conductive self-assembly structures are constructed and the particle size and specific surface area of the material are adjusted.
[0050] The present invention realizes the self-assembly of silicon-carbon and graphene sheets through a simple process flow, and enables graphene and conductive carbon black to be compounded with the prepared silicon-carbon material through a slurrying and homogenization process. By adding a suitable recarburizer, the stability of the negative electrode material is improved, the specific surface area is reduced, and the long-cycle stability is improved. A conductive structure with excellent electronic and ionic conductivity, a conductive intercalation layer between submicron silicon spheres, an outer layer wrapped with graphene sheets, and rich in pitch-derived carbon is constructed. A multi-granulated silicon-carbon material with a self-assembled conductive structure is developed, which has a moderate specific surface area, high first coulombic efficiency, good long-cycle performance, and good rate performance.
[0051] The multi-granulated silicon-carbon material with a self-assembled conductive structure of the present invention is obtained by coating a graphite core with a loose, porous, and conductive intercalated silicon-carbon shell layer, which is obtained by secondary annealing and calcination under a protective atmosphere; the shell layer is formed by self-assembly of a submicron-scale silicon-carbon precursor after primary annealing and calcination, and secondary annealing; the outer layer of the material is formed by self-assembly and wrapping the graphene covering layer on the surface of the particles during secondary annealing. The micron porous silicon sphere precursor is formed by primary granulation of nano-silicon powder, and the precursor particles serve as the silicon skeleton of the porous silicon spheres, which are assembled into multi-scale distributed porous silicon sphere aggregates through secondary granulation, and a multi-dimensional conductive network exists in the aggregates. The preparation method of the multi-granulated silicon-carbon material with a self-assembled conductive structure of the present invention comprises the following steps:
[0052] 1) placing a carbon source with a softening point of 150-200° C. and nano-silicon powder in a mixer to mix the mixture to obtain a uniformly mixed material; placing the mixture in a high-temperature coating machine for primary sintering, and passing through a 200-500 mesh sieve to obtain submicron-sized primary granulated silicon-carbon precursor microspheres;
[0053] 2) The primary granulated silicon-carbon precursor microspheres, recarburizer, graphene oxide, cryptocrystalline graphite, and graphite with D50=9-12 μm are placed in a mixer and mixed evenly, and the materials are added to a high-temperature coating machine for secondary sintering to obtain a secondary granulated silicon-carbon composite material.
[0054] The multi-granulated silicon-carbon material described in the present invention also includes tertiary granulation of the secondary granulated silicon-carbon composite material or surface modification of the secondary granulated silicon-carbon composite material; the tertiary granulation of the secondary granulated silicon-carbon composite material is obtained by mixing the secondary granulated silicon-carbon composite material, water-soluble phenolic resin, distilled water, and anhydrous ethanol, stirring and evaporating the mixture; a layer of amorphous carbon is added to the secondary granulated silicon-carbon composite material; the surface modification of the secondary granulated silicon-carbon composite material is obtained by adding the secondary granulated silicon-carbon composite material, distilled water, and a polymer surfactant into a dryer, stirring, drying, and sieving to obtain a silicon-carbon composite material with a hydrophilic surface.
[0055] In the above-mentioned technical measures, primary granulation forms submicron silicon-carbon microspheres; secondary granulation forms a coating of submicron silicon-carbon microspheres on the graphite surface, while simultaneously constructing a conductive structure through the self-assembly of small-sized cryptocrystalline graphite intercalations. Tertiary granulation uses the secondary granulation particles, which are then coated with a hydrophilic amorphous carbon layer by dissolving a water-soluble resin and evaporating it. This amorphous carbon layer, unlike carbon sources such as asphalt, has a highly hydrophilic carbon layer. Surface modification involves coating the surface of the secondary granulation particles with a hydrophilic layer by using a solvent surfactant and then evaporating it.
[0056] The reduced graphene oxide, graphene oxide, and cryptocrystalline graphite in the present invention were all sourced from Guangdong Junchi New Energy Co., Ltd. PAA was sourced from Sichuan Yindile Materials Technology Group Co., Ltd.; and single-walled carbon nanotubes were sourced from Foshan Greifen New Energy Co., Ltd.
[0057] In the present invention, the temperature rise within a certain time range is controlled to be uniform.
[0058] Example 1
[0059] A method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure comprises the following steps:
[0060] Take 36 kg of 325-mesh metallic silicon powder and disperse it in a stirring kettle containing 114 kg of diethylene glycol dimethyl ether solvent. Stir and disperse it at a speed of 600 r / min for 1 hour. The suspension is pumped into a sand mill through a diaphragm pump and sand milled at a speed of 1250 r / min for 4 hours. After drying, nano-silicon powder is obtained. The test is carried out by Jinan Micro-Nano Particle Size Tester Winner2018, and Dv50 = 550 ± 20 nm is controlled according to the sand milling time.
[0061] Preparation of precursor by one-time granulation: 1.275 kg of the obtained nano-silicon powder and 225 g of asphalt crushed by a pulverizer are taken, added into a high-speed mixer, and stirred and dispersed; after discharging, the powder is added into a coating machine for one-time granulation, the stirring speed of the coating machine is controlled at 20 r / min, argon gas is introduced through a high-pressure gas cylinder, and heating is started after the oxygen content drops to 1-5 ppm; during the heating process, the temperature is raised from 0 to 180°C for 60 minutes, kept at 180°C for 2 hours, raised from 180 to 300°C for 60 minutes, raised from 300°C to 500°C for 40 minutes, and kept at 500°C for 2 hours to obtain one-time granulated silicon-carbon precursor microspheres.
[0062] Secondary granulation: Take 1 kg of the obtained primary granulation silicon-carbon precursor microspheres, 100 g of asphalt, 100 g of graphene oxide, 200 g of cryptocrystalline graphite, and 400 g of Dv50 = 10 μm graphite, mix them uniformly, and add them to a high-temperature coating machine for secondary granulation. The heating program is 0-180 ° C heating for 60 min, keeping at 180 ° C for 2 h, 180-400 ° C heating for 44 min, keeping warm for 1 h, 400 ° C ~ 900 ° C heating for 100 min, and keeping warm at 900 ° C for 2 h. The protective atmosphere during the high-temperature carbonization process is argon, and the oxygen content throughout the process is <5 ppm. The secondary granulated silicon-carbon composite material is obtained by discharging.
[0063] Surface modification: Take 10 kg of secondary granulated silicon-carbon composite material and 200 g of polyethylene glycol with a molecular weight of 2000, add them into a stirring tank, add distilled water and stir for 1 hour, add the liquid into a dryer and evaporate to dryness, sieve the material after discharge, and obtain a surface-modified secondary granulated silicon-carbon composite material with a self-assembled conductive structure.
[0064] Weigh 0.07 g of surface-modified secondary granulated silicon-carbon composite material with self-assembled conductive structure, 0.014 g of conductive carbon black super P, 0.25 g of single-walled carbon nanotubes, 0.0075 g of sodium carboxymethyl cellulose binder, and 0.1875 g of PAA binder, add 2.5 ml of deionized water, and stir magnetically for 1 hour. The material is coated on copper foil (diameter 14 mm) with a loading of 0.6 mg, dried, and pressed into a sheet to form an electrode. A metal lithium sheet is used as the counter electrode and assembled into a CR 2016 button battery in a glove box.
[0065] Figure 1 This is the XRD pattern of the surface-modified secondary granulated silicon-carbon composite material with a self-assembled conductive structure prepared in Example 1. The nano-silicon powder used therein is consistent with JCPDS No. 27-1402, and no other obvious impurity peaks appear, indicating that the material prepared by this process is of high purity.
[0066] Figure 2 The transmission electron micrographs of the self-assembled structure prepared in Example 1 are shown in Figures a) and b) respectively, which are transmission electron micrographs of a thin layer of large graphene oxide sheets with abundant wrinkles wrapped in a composite material at different high magnifications. It can be observed that graphene oxide is present in the outermost layer of the material; Figures c) and d) respectively show cryptocrystalline graphite conductive intercalations at different magnifications, and the layered structure of graphite can be seen. This graphite layered structure is a self-assembled conductive intercalation layer of the material, which is used to accelerate the electronic / ionic conductivity between the silicon-carbon precursor particles.
[0067] Figure 3 The SEM images of the secondary granulated silicon-carbon material with self-assembled conductive structure obtained in Example 1 are shown in Figure e) as a fully wrapped silicon-carbon self-assembled conductive material with graphite as the core, and the upper right image of Figure f) is a small particle of graphite. Figure 3 As shown in the figure, large-particle graphite is used as the granulation core, and the primary particles are attached to the outer layer of graphite through the bonding effect of asphalt. Figure 3 It can be seen that the curled structure around the silicon-carbon monomer prepared in this embodiment is formed by asphalt-derived carbon wrapped on the surface of the crushed graphene sheet, and the silicon particles are wrapped by the asphalt-derived carbon and curled graphene, forming an asphalt-coated nano-silicon composite self-assembled structure with graphene conductive skeleton as the main body.
[0068] Figure 6Infrared spectrum of the secondary granulated silicon-carbon material with a self-assembled conductive structure prepared in Example 1. The Si-OC bond contributes to the structural stability of the silicon-carbon material. Introducing this covalent bond during the sintering process of an oxygen-containing conductive agent such as graphene oxide with the silicon-carbon material can form a more stable chemical structure, helping to improve the overall stability of the negative electrode material. This stability helps reduce material pulverization due to volume changes during charge and discharge, thereby increasing the cycle life of the battery.
[0069] Figure 7 This is the high-resolution XPS spectrum of Si 2p of the secondary granulated silicon-carbon material with a self-assembled conductive structure prepared in Example 1. This spectrum proves the existence of Si-OC bonds, indicating that there is a chemical bond between the surface carbon layer and silicon, rather than a simple physical bond.
[0070] Figure 8 This is the XPS high-resolution spectrum of C1s of the secondary granulated silicon-carbon material with self-assembled conductive structure obtained in Example 1. There are three peaks at 284.19, 284.77, and 285.92 eV, corresponding to the presence of C-Si, CC / C=C, and CO bonds, respectively. Figure 8 and Figure 7 It can be judged that there are multiple bond bridges between the carbon layer and the internal silicon-based material, which is consistent with the infrared spectrum. Figure 6 Mutual evidence.
[0071] Example 2
[0072] A method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure comprises the following steps:
[0073] Take 36 kg of 325-mesh metallic silicon powder and disperse it in a stirring kettle containing 114 kg of diethylene glycol dimethyl ether solvent. Stir and disperse it at a speed of 600 r / min for 1 hour. The suspension is pumped into a sand mill through a diaphragm pump and sand milled at a speed of 1250 r / min for 4 hours. After drying, nano-silicon powder is obtained. The test is carried out by Jinan Micro-Nano Particle Size Tester Winner2018, and Dv50 = 550 ± 20 nm is controlled according to the sand milling time.
[0074] 1.275 kg of the obtained nano-silicon powder, 125 g of asphalt crushed by a pulverizer, and 100 g of glucose were added to a high-speed blender and stirred to disperse. After discharging, the powder was added to a coating machine with a stirring speed of 20 r / min. Argon gas was introduced through a high-pressure gas cylinder. After the oxygen content dropped to 1-5 ppm, heating was started. The heating process took 80 minutes to raise the temperature from 0 to 300°C, followed by 60 minutes at 300°C, 60 minutes at 300°C, 80 minutes at 500°C, and 2 hours at 900°C. After high-temperature carbonization, the material was discharged and bagged to obtain sintered, single-granulation silicon-carbon precursor microspheres.
[0075] Take 1 kg of the obtained graphene-based submicron silicon sphere precursor, 100 g of asphalt, 50 g of glucose, 200 g of cryptocrystalline graphite, 100 g of graphene oxide, and 400 g of Dv50=10 μm graphite, mix them evenly, and add them to a high-temperature coating machine for secondary granulation. The heating program is 0-180°C heating for 60 min, keeping at 180°C for 2 h, 180-400°C heating for 44 min, keeping at 1 h, 400°C-900°C heating for 100 min, and keeping at 900°C for 2 h. The protective atmosphere during the high-temperature carbonization process is argon, and the oxygen content throughout the process is <5 ppm. The discharged material obtains a secondary granulated silicon-carbon composite material.
[0076] 1 kg of secondary granulated silicon-carbon composite material and 20 g of polyethylene glycol were added to a stirring tank, distilled water was added and stirred for 1 hour, the liquid was added to a dryer and evaporated to dryness, and the material was sieved after discharge to obtain a surface-modified secondary granulated silicon-carbon composite material with a self-assembled conductive structure.
[0077] Weigh 0.07 g of silicon-carbon composite material, 0.0145 g of conductive carbon black super P, 0.125 g of single-walled carbon nanotubes, 0.0075 g of sodium carboxymethyl cellulose binder, and 0.1875 g of PAA binder, add 2.5 ml of deionized water, and stir magnetically for 1 hour. The material is coated on copper foil (diameter 14 mm) with a loading of 0.6 mg, dried, and pressed into a sheet to form an electrode. A metal lithium sheet is used as the counter electrode and assembled into a CR 2016 button battery in a glove box.
[0078] Example 3
[0079] A method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure comprises the following steps:
[0080] Take 24 kg of 325-mesh metallic silicon powder and disperse it in a stirring tank containing 114 kg of diethylene glycol methyl ethyl ether solvent. Stir and disperse it at a speed of 600 r / min for 1 hour. The suspension is pumped into a sand mill through a diaphragm pump and sand milled at a speed of 1350 r / min for 3 hours. After drying, nano-silicon powder is obtained. The test is performed by Jinan Micro-Nano Particle Size Tester Winner2018, and Dv50 = 550 ± 20 nm is controlled according to the sand milling time.
[0081] 1.275 kg of the aforementioned nano-silicon powder, 225 g of pulverized asphalt, and 150 g of needle coke were added to a high-speed blender and stirred for dispersion. The powder was then added to a ball mill at a ball-to-material ratio of 3:1 and milled for 8 hours. The resulting mixture was then added to a coating machine, stirred at 20 rpm, and introduced with nitrogen or argon via a high-pressure gas cylinder. After the oxygen content dropped to 1-5 ppm, heating was initiated. The temperature was raised from 0 to 300°C for 80 minutes, followed by a 60-minute hold at 300°C, a 60-minute hold at 300°C, a 60-minute hold at 300°C, a 50-minute hold at 500°C, a 80-minute hold at 500°C, and a 2-hour hold at 900°C. After high-temperature carbonization and primary granulation, the resulting mixture was bagged to yield sintered primary granulated silicon-carbon precursor microspheres.
[0082] Take 1 kg of the above-mentioned primary granulated silicon-carbon precursor microspheres, 100 g of asphalt, 400 g of graphite with Dv50 = 10 μm, 100 g of cryptocrystalline graphite, and 100 g of graphene oxide, mix them evenly, and add them to a high-temperature coating machine for secondary granulation. The heating program is 0-180°C heating for 60 min, keeping warm at 180°C for 2 h, heating at 180-400°C for 44 min, keeping warm for 1 h, heating at 400°C to 900°C for 100 min, and keeping warm at 900°C for 2 h. The protective atmosphere during the high-temperature carbonization process is argon, and the oxygen content throughout the process is <5 ppm. The discharged material obtains a secondary granulated silicon-carbon material with a self-assembled conductive structure.
[0083] Weigh 0.07 g of secondary granulated silicon-carbon material with a self-assembled conductive structure, 0.0145 g of conductive carbon black super P, 0.125 g of single-walled carbon nanotubes, 0.0075 g of sodium carboxymethyl cellulose binder, and 0.1875 g of PAA binder, add 2.5 ml of deionized water, and stir magnetically for 1 hour. The material is coated on a copper foil (diameter 14 mm) with a loading of 0.6 mg, dried, and pressed into a sheet to form an electrode. A metal lithium sheet is used as the counter electrode and assembled into a CR 2016 button battery in a glove box.
[0084] Example 4
[0085] A method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure comprises the following steps:
[0086] Take 36 kg of 325-mesh metallic silicon powder and disperse it in a stirring tank containing 114 kg of diethylene glycol methyl ethyl ether solvent. Stir and disperse it at a speed of 600 r / min for 1 hour. The suspension is pumped into a sand mill through a diaphragm pump and sand milled at a speed of 1250 r / min for 4 hours. After drying, nano-silicon powder is obtained. The test is carried out by Jinan Micro-Nano Particle Size Tester Winner2018, and Dv50 = 550 ± 20 nm is controlled according to the sand milling time.
[0087] Preparation of single-granulation silicon-carbon precursor microspheres: take 1.275 kg of the obtained nano-silicon powder, 225 g of asphalt crushed by a pulverizer, and 100 g of powdered phenolic resin, add them into a high-speed mixer, and stir and disperse; after discharging, add the powder into a coating machine for single granulation, control the stirring speed to 20 r / min, introduce argon gas through a high-pressure gas cylinder, wait until the oxygen content drops to 1-5 ppm, and then start heating; during the heating process, heat from 0 to 180°C for 60 minutes, keep at 180°C for 2 hours, heat from 180 to 300°C for 60 minutes, heat from 300°C to 500°C for 40 minutes, and keep at 500°C for 2 hours to obtain single-granulation silicon-carbon precursor microspheres.
[0088] Preparation of secondary granulated silicon-carbon composite materials: Take 1 kg of the obtained primary granulated silicon-carbon precursor microspheres, 300 g of asphalt, 100 g of graphene oxide, 200 g of cryptocrystalline graphite, and 400 g of Dv50=10 μm graphite, mix them uniformly, and add them to a high-temperature coating machine for secondary granulation. The heating program is 0-180°C heating for 60 min, keeping at 180°C for 2 h, 180-400°C heating for 44 min, keeping at 1 h, 400°C-900°C heating for 100 min, and keeping at 900°C for 2 h. The protective atmosphere during the high-temperature carbonization process is argon, and the oxygen content throughout the process is <5 ppm. The discharged material obtains a secondary granulated silicon-carbon composite material with a self-assembled conductive structure.
[0089] Weigh 0.07 g of secondary granulated silicon-carbon composite material, 0.0145 g of conductive carbon black super P, 0.125 g of single-walled carbon nanotubes, 0.0075 g of sodium carboxymethyl cellulose binder, and 0.1875 g of PAA binder, add 2.5 ml of deionized water, and stir magnetically for 1 hour. The material is coated on copper foil (diameter 14 mm) with a loading of 0.6 mg, dried, and pressed into a sheet to form an electrode. A metal lithium sheet is used as the counter electrode and assembled into a CR 2016 button battery in a glove box.
[0090] Example 5
[0091] A method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure comprises the following steps:
[0092] Take 36 kg of 325-mesh metallic silicon powder and disperse it in a stirring tank containing 114 kg of diethylene glycol methyl ethyl ether solvent. Stir and disperse it at a speed of 600 r / min for 1 hour. The suspension is pumped into a sand mill through a diaphragm pump and sand milled at a speed of 1250 r / min for 4 hours. After drying, nano-silicon powder is obtained. The test is carried out by Jinan Micro-Nano Particle Size Tester Winner2018, and Dv50 = 550 ± 20 nm is controlled according to the sand milling time.
[0093] Preparation of single-granulation silicon-carbon precursor microspheres: take 1.275 kg of the obtained nano-silicon powder, 200 g of asphalt crushed by a pulverizer, and 100 g of glucose, add them into a high-speed mixer, and stir and disperse; after discharging, add the powder into a coating machine for single granulation, control the stirring speed to 20 r / min, introduce argon gas through a high-pressure gas cylinder, wait until the oxygen content drops to 1-5 ppm, and then start heating; during the heating process, heat from 0 to 180°C for 60 minutes, keep warm at 180°C for 2 hours, heat from 180 to 300°C for 60 minutes, heat from 300°C to 500°C for 40 minutes, and keep warm at 500°C for 2 hours to obtain single-granulation silicon-carbon precursor microspheres.
[0094] Preparation of secondary granulated silicon-carbon composite materials: Take 1 kg of the obtained primary granulated silicon-carbon precursor microspheres, 300 g of asphalt, 100 g of graphene oxide, 200 g of cryptocrystalline graphite, and 400 g of Dv50=10 μm graphite, mix them uniformly, and add them to a high-temperature coating machine for secondary granulation. The heating program is 0-180°C heating for 60 min, keeping at 180°C for 2 h, 180-400°C heating for 44 min, keeping at 1 h, 400°C-900°C heating for 100 min, and keeping at 900°C for 2 h. The protective atmosphere during the high-temperature carbonization process is argon, and the oxygen content throughout the process is <5 ppm. The discharged material obtains a secondary granulated silicon-carbon composite material with a self-assembled conductive structure.
[0095] Three-time coating of phenolic resin: take 50g of secondary granulated silicon-carbon composite material, add 10g of water-soluble phenolic resin, add 500ml of distilled water, 50g of anhydrous ethanol, stir for 1h, evaporate the mixed solvent of distilled water and anhydrous ethanol to obtain a mixture of water-soluble resin wrapped silicon-carbon composite material, pour it into a porcelain boat and carbonize it at a high temperature of 900℃ to obtain a three-time coated silicon-carbon composite material. The water-soluble phenolic resin comes from Shanghai Yierfu Company.
[0096] Weigh 0.07g of the triple-coated silicon-carbon composite, 0.0145g of conductive carbon black Super P, 0.125g of single-walled carbon nanotubes, 0.0075g of sodium carboxymethyl cellulose binder, and 0.1875g of PAA binder, add 2.5ml of deionized water, and stir magnetically for 1h. The material is coated on a copper foil (14mm diameter) with a loading of 0.6mg, dried, and pressed into a sheet to form an electrode. A metal lithium sheet is used as the counter electrode, and assembled into a CR 2016 button cell in a glove box. The CR2016 button cell process is the same as in Example 1.
[0097] Comparative Example 1
[0098] A method for preparing a one-step granulation silicon-carbon material comprises the following steps:
[0099] (1) 1.275 kg of nano-silicon powder prepared under the same conditions as in Example 1, 225 g of asphalt crushed by a crusher, and 150 g of graphene oxide were added to a high-speed stirrer and stirred and dispersed at a frequency of 20 Hz for 1 h.
[0100] (2) After discharging, the above materials are added to a high-temperature coating machine with a stirring speed of 20 r / min, and nitrogen or argon is introduced through a high-pressure gas cylinder. After the oxygen content is reduced to 1-5 ppm, heating is started; during the heating process, the temperature is raised from 0 to 180°C for 60 minutes, kept at 180°C for 2 hours, raised from 180 to 300°C for 60 minutes, raised from 300°C to 900°C for 100 minutes, and kept at 900°C for 2 hours to obtain a single-granulated silicon-carbon material.
[0101] The CR2016 button battery process and test conditions are the same as those in Example 1.
[0102] Comparative Example 2
[0103] A large-scale preparation of a high-performance silicon-carbon composite material and a composite self-assembly structure design thereof include the following steps:
[0104] (1) Take 1.275 kg of the nano-silicon powder in Example 1, 225 g of asphalt crushed by a crusher, 100 g of asphalt, 100 g of graphene oxide, and 400 g of graphite, add them to a high-speed blender, and stir and disperse; after discharging, add the powder to a ball mill with a ball-to-material ratio of 6:1 and ball mill for 8 hours.
[0105] (2) Add the ball-milled nano-silicon powder and asphalt mixture to a coating machine, start stirring at a speed of 20 r / min, introduce nitrogen or argon through a high-pressure gas cylinder, wait for the oxygen content to drop to 1-5 ppm, and then start heating; during the heating process, the temperature is raised from 0 to 300°C for 80 minutes, kept at 300°C for 60 minutes, raised from 300 to 500°C for 60 minutes, raised from 500 to 900°C for 80 minutes, and kept at 900°C for 2 hours. After the high-temperature carbonization is completed, the material is discharged and bagged to obtain the sintered product.
[0106] Weigh 0.07 g of unmodified silicon-carbon composite material, 0.0145 g of conductive carbon black super P, 0.125 g of single-walled carbon nanotubes, 0.0075 g of sodium carboxymethyl cellulose binder, and 0.1875 g of PAA binder, add 2.5 ml of deionized water, and stir magnetically for 1 hour. The material is coated on copper foil (diameter 14 mm) with a loading of 0.6 mg, dried, and pressed into a sheet to form an electrode. A metal lithium sheet is used as the counter electrode and assembled into a CR 2016 button battery in a glove box.
[0107] Figure 4 This is a scanning electron microscope image of graphene-based particles prepared using only one granulation step in Comparative Example 2. The graphene corrugated structure and large lamellar structure can be observed in the figure. The silicon-carbon material is attached to the graphene corrugated structure. The mechanical properties of graphene itself can help the silicon-carbon material maintain contact sites with the material during the volume change process of charge and discharge expansion and contraction. This structural design is conducive to improving the long-term cycle stability of the material. However, this structure only uses a single coating, and the material structure has the problem of insufficient packaging, and the capacity retention rate is lower than that of the embodiment.
[0108] Comparative Example 3
[0109] A large-scale preparation of a high-performance silicon-carbon composite material and a composite self-assembly structure design thereof include the following steps:
[0110] (1) Take 1 kg of the silicon-carbon precursor material of Example 1 and use vapor deposition to carbon-coat the surface of the material to form a uniform carbon layer wrapped by a small molecule gas carbon source. The experimental temperature is 760°C, and the vapor deposition coating carbon content accounts for 10% of the total weight of the sample.
[0111] (2) 1 kg of CVD silicon-carbon composite material and 20 g of polyethylene glycol were added to a stirring tank, distilled water was added and stirred for 1 hour, the liquid was added to a dryer and evaporated to dryness, and the material was sieved after discharge to obtain the CVD silicon-carbon composite material of comparative example 3.
[0112] Weigh 0.07 g of CVD silicon-carbon composite material, 0.0145 g of conductive carbon black super P, 0.125 g of single-walled carbon nanotubes, 0.0075 g of sodium carboxymethyl cellulose binder, and 0.1875 g of PAA binder, add 2.5 ml of deionized water, and stir magnetically for 1 hour. The material is coated on a copper foil (diameter 14 mm) with a loading of 0.6 mg. After drying, the material is pressed into a sheet to form an electrode. A metal lithium sheet is used as the counter electrode and assembled into a CR 2016 button battery in a glove box.
[0113] Performance Testing
[0114] The materials prepared by the above-mentioned embodiments and comparative example steps were characterized by thermogravimetric analysis (TG), X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy (Raman), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR) to analyze the morphology, component content, and chemical bond type of the materials.
[0115] X-ray diffraction was performed using a German D8 Advance X-ray diffractometer to test and characterize the materials. The radiation source was a Cu target and the wavelength of the radiation was λ CuKα =0.15406nm, the test angle was 5°≤2θ≤90°, the test voltage was 40kV, and the current was 40mA. The Fourier transform infrared spectroscopy was performed using a German Bruker Tensor with a collection range of 0-3000cm -1 Specific surface area analysis was performed using a Beijing Best 3H-200PSI instrument with N2 as the adsorption gas. X-ray photoelectron spectroscopy was performed using a Kratos Axis UltraDLD. Scanning electron microscopy (SEM) using a German LEO 1530VP cold-field SEM was used to analyze the micromorphology of the material. Transmission electron microscopy (TEM) using a Japanese JEM-2100HR was used to observe the internal structural characteristics of the material.
[0116] The materials prepared by the above-mentioned embodiments and comparative example steps were subjected to constant current charge and discharge, rate performance testing, impedance and long cycle testing to study the surface resistance, long cycle stability, resistance to large current interference and lithium storage mechanism of the materials.
[0117] The present invention mainly improves the traditional sand-milled silicon-coated carbon process to prepare a silicon-carbon composite material with uniform carbon coating, moderate specific surface area, high specific capacity, environmental friendliness and low cost. It realizes the self-assembly of silicon carbon and graphene through a simple process, explores the process path for mass preparation of graphene composite silicon-carbon materials, and explores the effect of increased carbon content on the rate performance of the material through subsequent secondary coating. After the batteries prepared in the above embodiments were set aside for 24 hours, a battery tester (Shenzhen Xinwei) and BTS8.0.0 software were used. The test temperature was 25°C and the current density was 0.2-20A·g-1. Constant current charge and discharge (discharge cut-off voltage 0.01V, charge cut-off voltage 2V) were used for various types of batteries to test the long-term cycle performance of the batteries. The electrochemical properties of the examples and comparative samples are detailed in Table 1. Table 1 involves 5 examples and 3 comparative examples of the preparation of multiple granulated silicon-carbon materials with self-assembled conductive structures. Examples 1 and 2 used a secondary coating process to construct a self-assembled conductive structure and performed surface modification to obtain a surface-modified secondary granulated silicon-carbon composite material with a self-assembled conductive structure; Examples 3 and 4 both used a secondary coating process to construct a self-assembled conductive structure. Example 5 added a water-soluble resin to Example 1, thereby coating the surface of the secondary granulated particles with a layer of hard carbon to further enhance the material's resistance to silicon expansion stress, resulting in a tertiary coated silicon-carbon composite material. Comparative Example 1 is a material that was granulated once without the addition of a multi-scale conductive agent. Comparative Example 2 is a material that was prepared using only a single coating process to combine multiple conductive agents with silicon nanoparticles using a single granulation process. Comparative Example 3 is a sample that was carbon-coated twice using a CVD method.
[0118] Table 1
[0119]
[0120] As shown in Table 1, Examples 1 to 5 are different from the existing materials in that they have a multiple self-assembled conductive structure with graphite as the core, and the first coulombic efficiency can reach more than 85.63%. -1 The current density is 785.78 mAh g after 600 cycles. -1 The above charge specific capacity, 58.09%-75.36% capacity retention rate, through multiple granulation process, the Dv50 after regulation is 5-10μm, the specific surface area of the embodiment can be controlled in 5.9121-17.82m 2 g -1 , can meet the requirements of national standard GB / T 38823-2020. -1The capacity retention rate of 58.09% to 75.36% of the composite material embodiments 1 to 5 using multiple granulation processes is significantly higher than that of 34.39% to 40.32% of the comparative examples 1 and 2 using only one granulation process.
[0121] The process used in Comparative Example 3 is the common CVD carbon coating method. The capacity retention rate of the material prepared by this method is 54.85% after 600 cycles, which seems to be not much different from the retention rate of 58.09% used in Technical Example 2 of the present invention. However, the comprehensive performance of the product obtained in Comparative Example 3 is still somewhat different from that of the present invention even in the worst case. More importantly, the coating process used in the secondary granulation of the present invention is simpler than the CVD process, has higher safety, and lower cost, and has significant advantages in the scale-up process.
[0122] Comparative Example 2 only used a single granulation and high-temperature sintering process, and the conductive agent and silicon nanoparticles were mixed using a simple process. The specific surface area of the material was 29.4520 m 2 g -1 The particle size Dv50 is 1.456 μm, which is smaller than the index of commercial silicon carbon (the Dv50 of commercial silicon carbon is generally between 5 and 10 μm, and 1.456 μm is too small, and it will agglomerate when pulped using a pulping machine). -1 The current density of 1000 cycles was only 529.34 mAh g -1 mAh g -1 The charge capacity and capacity retention rate of 34.39% are better than those of Example 2 of the present invention. -1 The current density of 1000 cycles was only 874.62 mAh g -1 mAh g -1 The charge specific capacity and capacity retention rate of 58.09% are achieved; the preparation method of the multi-granulated silicon-carbon material with a self-assembled conductive structure of the present invention significantly improves the rate performance and material cycle retention rate.
[0123] Figure 5 This is a long cycle performance diagram of the surface modified secondary granulated silicon-carbon composite material with self-assembled conductive structure in Example 1. -1 The current density of 1000 cycles still has 1047.08 mAh g -1 The charge capacity is 861.94 mAh g after 1000 cycles at this current. -1 The charge capacity is high and has excellent long cycle stability. In Table 1, the long cycle performance of 2Ag in Example 1 -1At a current density of 4A, the capacity retention rate after 600 cycles is higher than 60%, which is 20% higher than that of comparative example 1, indicating that the stability of the embodiment is high; the rate performance is good: the embodiment has a high current density such as 4A. -1 8Ag -1 Under the condition of 1000mAh, the capacity is still 750mAh g -1 The above results show that the capacity retention rate after 300 cycles is 70%, which is significantly higher than the capacity and retention rate of comparative example 1. Figure 10 Rate performance test, 20Ag -1 At a current density of 1.5 mAh g, the material of Example 1 still has a current density higher than 500 mAh g -1 The capacity retention rate is as follows. Through the above comparison, it is proved that the material with self-assembled conductive structure composited by secondary granulation has excellent structural performance in resisting large current impact compared with the material without secondary granulation. By adding conductive agents of different scales, the self-assembled conductive structure has more electron / ion channels and conductive sites, which improves the rate performance while solving the capacity attenuation problem caused by loss of contact due to pulverization during long-term cycling of silicon-based materials.
[0124] The data of Example 1 and Comparative Example 1 show that the multiple self-assembly structure constructed on the basis of secondary granulation has significant advantages in the cyclic stability of the material. -1 After 600 cycles at a current density of , the primary particles have only a capacity retention rate of 40.32%, which is lower than the 73.50% of the sample after secondary granulation. In terms of rate performance, Example 1 has a capacity retention rate of 4Ag -1 With 8Ag -1 There is no significant difference in the remaining charge capacity after 300 cycles at a high current density, which proves that the structure has structural advantages in resisting the impact of high current density. Due to the use of secondary coating technology and multi-scale conductive structure, when electrons / ions migrate at a faster speed at a high rate, they are conducted through the self-assembled conductive structure, such as cryptocrystalline graphite intercalation to ensure rapid conduction of electrons / ions between silicon precursors, and large layers of graphene to ensure that there is a fast conductive layered structure between the large particles of the secondary coating of the material, and the active material silicon can combine with lithium ions in a shorter time to release capacity; effective secondary coating can alleviate the expansion of silicon materials, and the core of the graphite particles as internal support improves the pulverization problem of isolated silicon-based materials. The wrapping of the external carbon layer and the self-assembled conductive structure realize the relief of the expansion stress of the silicon material, which can alleviate the expansion rate of the battery cell in actual application. In the application fields of consumer batteries that require high-rate instantaneous discharge, such as e-cigarettes and emergency power supplies, this structural design can play a role in protecting the negative electrode of the material.
[0125] Figure 9 The surface modified secondary granulated silicon-carbon material with self-assembled conductive structure prepared in Example 1 was heated at 25°C and 0.2Ag-1 The charge-discharge capacity curve of the first three cycles at a current density of . The figure shows that the voltage window is 0.01-2V, the first coulombic efficiency of the material is greater than 88%, and the charge capacity is 2062.90mAh g -1 .
[0126] Figure 10 The secondary granulated silicon-carbon material with self-assembled conductive structure prepared in Example 1 and Example 3 is 0.5-20Ag -1 The figure shows the rate performance of the material. The reversible capacity of the material under different current shocks is tested from a low current to a high current, and the 20Ag -1 The current density returned to 1A after the shock -1 The reversible specific capacity after the current density of 1Ag was -1 The reversible specific capacity of the current density test was found to have no capacity attenuation, proving that the material had no structural damage after being subjected to a large current shock, had strong resistance to large current shocks, and had good rate performance.
[0127] As can be seen from the above embodiments, the present invention has the following characteristics:
[0128] The composite material prepared by the present invention is a graphite core material with an outer layer of silicon carbon wrapped therein, and a structure in which graphene oxide is a conductive network and cryptocrystalline graphite is a conductive intercalation layer. -1 and 8Ag -1 It exhibits excellent cycling stability at high current density, indicating that the adhesion of asphalt-derived carbon on graphene is conducive to the formation of a more tightly wrapped conductive carbon layer in the silicon-carbon composite graphene material, reflecting the role of this structure in alleviating silicon expansion stress. The successful preparation of the self-assembled structure can be observed based on the transmission electron microscopy and scanning electron microscopy results.
[0129] The silicon-carbon composite graphene material of the present invention is a high-performance lithium-ion battery negative electrode material with the advantages of excellent lithium ion transmission rate, long cycle stability, rate performance and high specific capacity. It is suitable for the field of new energy vehicle power batteries and has significant advantages in the field of consumer batteries. It is particularly suitable for emergency power supplies that require instantaneous high-rate discharge.
[0130] The above embodiments are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure, characterized in that The steps include: 1) placing a carbon source with a softening point of 150-200° C. and nano-silicon powder in a mixer to mix the mixture to obtain a uniformly mixed material; adding the mixture to a high-temperature coating machine for primary sintering, and passing through a 200-500 mesh sieve to obtain submicron-scale primary granulated silicon-carbon precursor microspheres; 2) The primary granulated silicon-carbon precursor microspheres, the recarburizer, the graphene oxide, the cryptocrystalline graphite, and the D50=9-12 μm graphite are placed in a mixer and mixed evenly, and the materials are added to a high-temperature coating machine for secondary sintering to obtain a secondary granulated silicon-carbon composite material.
2. The method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure according to claim 1, characterized in that: The multi-granulated silicon-carbon material further comprises tertiary granulation of the secondary granulated silicon-carbon composite material or surface modification of the secondary granulated silicon-carbon composite material; The three-time granulation of the secondary granulated silicon-carbon composite material is obtained by mixing the secondary granulated silicon-carbon composite material, water-soluble phenolic resin, distilled water and anhydrous ethanol, stirring and evaporating to dryness; a layer of amorphous carbon is added to the secondary granulated silicon-carbon composite material; The surface modification of the secondary granulated silicon-carbon composite material is to add the secondary granulated silicon-carbon composite material, distilled water and a polymer surfactant into a dryer, stir, dry and sieve to obtain a silicon-carbon composite material with a hydrophilic surface.
3. The method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure according to claim 2, characterized in that: In the third granulation, the mass ratio of the secondary granulation silicon-carbon composite material, water-soluble phenolic resin, distilled water and anhydrous ethanol is 5: (1-2): (8-12): (0.5-2); In the surface modification, the polymer surfactant is one or more of polyethylene glycol, polyvinyl pyrrolidone, polyoxyethylene fatty acid ester, sodium carboxymethyl cellulose, and polyoxyethylene fatty acid ester; the mass ratio of the secondary granulated silicon-carbon composite material, distilled water, and polymer surfactant is (2-3):10:(0.04-0.06).
4. The method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure according to claim 1, characterized in that: In step 1), the carbon source with a softening point of 150 to 200° C. is one or more of asphalt, phenolic resin and glucose; the mass ratio of the carbon source to the nano-silicon sheet is 1:5 to 2:5; In step 2), the recarburizer is one or more of graphite, glucose, needle coke, and phenolic resin; the mass ratio of the primary granulated silicon-carbon precursor microspheres, the recarburizer, graphene oxide, cryptocrystalline graphite, and graphite with D50=9-12 μm is 50:(2-4):(2-4):(10-20).
5. The method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure according to claim 4, characterized in that: The carbon source is crushed by a crusher before use; The cryptocrystalline graphite has a Dv50 of <1 μm; The graphene oxide has a thickness of less than 3 nm, a particle size distribution between 20 and 40 μm, and a specific surface area of 40 to 50 m 2 / g.
6. The method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure according to claim 1, characterized in that: In step 1), the heating program of the primary sintering is heating at 0-180°C for 1-2h, keeping at 180°C for 1-2h, heating at 180-300°C for 1-2h, heating at 300°C-500°C for 1-2h, and keeping at 500°C for 2-4h; In step 2), the temperature program of the secondary sintering is 0-180°C for 1-2h, 180°C for 2-4h, 180-400°C for 40-60min, 1-2h, 400-900°C for 100-160min, 900°C for 2-4h; Argon gas is added as a protective atmosphere during the primary sintering and secondary sintering processes, and the oxygen content is controlled at 1-5 ppm throughout the process.
7. The method for preparing a multi-granulated silicon-carbon material having a self-assembled conductive structure according to claim 1, characterized in that: The silicon powder is prepared by wet sand milling; the rotation speed of the wet sand milling is 1000-1500 r / min, the sand milling time is 2-6 hours, the particle size Dv50 of the silicon powder after grinding is controlled to be 400-600 nm, and the silicon powder is stored in vacuum packaging; the solvent for wet sand milling is selected from one or more of diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether and oleic acid, and the solid content is controlled to be 20-50% during sand milling.
8. A multi-granulated silicon-carbon material having a self-assembled conductive structure, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the multi-granulated silicon-carbon material with a self-assembled conductive structure as claimed in claim 8 in the preparation of negative electrode materials for lithium-ion batteries.
10. The use of the multi-granulated silicon-carbon material with a self-assembled conductive structure in the preparation of a negative electrode material for a lithium-ion battery according to claim 9, characterized in that: The method for preparing the negative electrode material for a lithium-ion battery comprises mixing a multi-granulated silicon-carbon material with a self-assembled conductive structure, conductive carbon black and / or single-walled carbon nanotubes, CMC and PAA, slurrying the mixture, and coating the mixture on a copper foil to obtain a negative electrode sheet for a lithium-ion battery; the mass ratio of the multi-granulated silicon-carbon material with a self-assembled conductive structure, carbon black and / or single-walled carbon nanotubes, CMC and PAA is (5-16):(3-2):(0.5-2):1.
Citation Information
Patent Citations
Silicon-carbon negative electrode material and preparation method thereof
CN113644252B
Flaky three-dimensional silicon carbon electrode and preparation method thereof
CN116799148A
Preparation method of graphene-based silicon carbon negative electrode material
CN117038984A
Composite graphite-silicon lithium ion battery cathode material and preparation method thereof
CN103560234A
Lithium ion battery silicon-carbon composite negative material and its preparation method
CN104332613A
Cited By
Conductive skin silicon carbon material and preparation method and application thereof
CN121601641A
Self-assembled elastic conductive silicon carbon microsphere, preparation method thereof and application of self-assembled elastic conductive silicon carbon microsphere in lithium ion battery
CN122426728A